Use of archaeological information in society - Huvila, Isto (Uppsala University, 2017)
Data was collected using a mixed qualitative-quantitative web survey, which was administered using E-lomake survey software. The survey included 20 questions of which 3 included multiple statements on a 5-point Likert-like scale. 12 of the questions were open-ended and the focus of both data collection and analysis was on qualitative understanding rather than quantification. The respondents were asked to describe and rate their experiences of the development-led archaeology process, usefulness and use of archaeological information, and to indicate the branch and size of the organisation they represented.

The sample is essentially a convenience sample of Finnish and Swedish organisations, which contracted archaeological investigations in 2013-2014. For Sweden, the names of the organisations were harvested semi- automatically using custom-written php-scripts from the PDF reports covering the chosen timeframe and available at the Samla database of the NHB (samla.raa.se). For Finland, the same data was collected from Muinaisjäännösten hankerekisteri (engl. Antiquities Project Registry) database (http://kulttuuriymparisto. nba.fi) maintained by the National Board of Antiquities of Finland. Email addresses of the organisations and, as possible, individuals working at relevant parts of the organisation (depending on the type of the organisation, generally planning, development and property management related functions) were collected using public online sources, including the websites of the organisations. Invitations were sent during the summer and autumn of 2015 to 241 Swedish organisations and 131 Finnish organisations. One reminder to participate in the survey was submitted to all organisations. Nine invitations were returned as definitely undeliverable.

In total 34 organisations participated in the survey, 14 from Finland and 20 from Sweden. Twenty of the 34 respondents classified their organisations as municipal which corresponds relatively well with the distribution of the organisations in the original population (126 of the 241 Swedish and 87 of the 131 Finnish organisations were municipalities, excluding municipal e.g. energy and water supply companies). Five of the 34 respondents represented construction companies, 3 organisations in the energy branch, 3 regional and 2 national public bodies. One organisation from the property development, mining and environmental consulting branches participated in the survey. Amounts of employess varied - eight of 34 organisations had less than 10, 14 of the 34 organizations had between 11 and 100, five of the 34 had between 101 and 999, and seven of the 34 organizations had over 1000 employees.

Especially for Sweden, it is important to note that the collection of reports is not complete, partly because only a part of the available reports contained information on the organisations who had contracted and/or financed investigations. It is also possible that the semi-automated harvesting process failed to find a small number of organisations. In addition, it is likely that in a number of organisations, the invitation did not reach the relevant respondents even if the invitation contained a request to forward it to a colleague if the recipient considered herself to be unable to take the survey. Therefore, even if the sampling approach was designed to reach a reasonable level of systematicity, coverage and comparability, the lack of a comprehensive project or central report registry in Sweden, technical issues, variation in the reporting of the contracting organisations, and the varying specificity of contact details mean that the final sample is closer to a convenience sample than a systematic cross section.

(Description from Huvila, I. Land developers and archaeological information. Open Information Science, 2017, 1(1), 71-90)

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för beskrivning.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Uppdragsarkeologisk information i samhället
Arkeologisen informaation käyttö yhteiskunnassa
Keywords: archaeological information; archaeological information; Archaeology; Archaeology; land developers; land developers; Library and Information Science; Library and Information Science; archaeology; archaeology; Archaeology; Arkeologi; Information Studies; Biblioteks- och informationsvetenskap